Adipocytes Promote Early Steps of Breast Cancer Cell Dissemination via Interleukin-8 - Vazquez Rodriguez, Gabriela; Abrahamsson, Annelie; Jensen, Lasse Dahl Ejby; Dabrosin, Charlotta (Frontiers in Immunology, 2018)
Fat is a major tissue component in human breast cancer. Whether breast adipocytes affect early stages of breast cancer metastasis is yet unknown. Breast cancer progression is dependent on angiogenesis and inflammation and interleukin-8 (IL-8) and vascular endothelial growth factor (VEGF) are key regulators of these events. Here we show that breast adipocytes increased dissemination of estrogen receptor positive (ER+) breast cancer cells in vivo in the zebrafish model of metastasis while dissemination of the more aggressive and metastatic breast cancer cells such as ER- were unaffected. While anti-VEGF and anti-IL-8 exhibited equal inhibition of angiogenesis at the primary tumor site, anti-IL-8 reduced breast cancer cell dissemination whereas anti-VEGF had minor effects on this early metastatic event. Mechanistically, overexpression of cell-adhesion molecules in breast cancer cells and neutrophils via IL-8 increased the dissemination of breast cancer cells. Importantly, the extracellular in vivo levels of IL-8 were 40-fold higher than those of VEGF in human breast cancer. Our results suggest that IL-8 is a clinical relevant and promising therapeutic target for human breast cancer.